Motivasi Pengguna dalam Menggunakan Media Sosial dan Keterlibatan dengan Iklan Media Sosial - Dhyana Paramita (OPSI, 2022)
In the marketing field, social media advertising has become powerful medium to market products and services. The purpose of this study is to analyze the connection that exists between user motivation and the engagement of social media advertisements. In addition to that, the purpose of this study is to determine which kinds of social media have the highest levels of user involvement. A cross-sectional design with a self-administered questionnaire is used for the research methodology. The Chi-square test developed by Pearson is used as the correlation test for the investigation. Non-random sampling is used for the selection of the population, with a minimum sample size of thirty master's students from Uppsala University serving as the selection criteria. According to the findings, there is no connection between user motivation with their engagement in the online advertising. In addition, when it comes to online advertising, Facebook and Instagram are the two platforms that have the highest level of user engagement. The findings also suggest that there is a significant positive relationship between the most used channels and user engagement to online advertising.